Interactive English Teaching Materials Based on Digital Literacy of Millennial Muslims - Aria Septi Anggaira; Suhono Suhono; Yeasy Agustina Sari; Nurul Aryanti; Aldi Permana Putra (AL-ISHLAH: Jurnal Pendidikan, 2022)
Research that compiles interactive textbooks based on digital literacy for high school is still limited, especially based on Islamic literacy for Madrasah Aliyah Students.  This research is the initial stage of a research development with 4D Models (Define, Design, Develop, and Disseminate) which aims to discover and analyze the needs of interactive teaching materials based on digital literacy of millennial Muslims in English subjects at Madrasah Aliyah. The subjects of this study were students of Islamic senior high schools (MAN) in Lampung Province, Islamic senior high school (MAN) 1 Kota Metro, Islamic senior high school (MAN) 1 Bandar Lampung, and Islamic senior high school (MAN) 1 Pringsewu. The number of respondents was 97 students.  The research data were obtained through a questionnaire consisting of 16 questions which is the development of four indicators., namely: students' needs for content/topics based on digital literacy of millennial Muslims, student needs related to four language skills (listening, speaking, reading, and writing) that are Islamic and digitally taught, students' needs for Islamic learning activities/processes, and students' needs for learning evaluation. The results  obtained an average of 80.9%. Thus, interactive teaching material based on the digital literacy of millennial Muslims is needed in English Learning at Madrasah  AliyahInteractive Teaching Material, Digital Literacy Millennial Muslim Generation)